2018
DOI: 10.18632/oncotarget.26157
|View full text |Cite
|
Sign up to set email alerts
|

The anti-cancer effect of retinoic acid signaling in CRC occurs via decreased growth of ALDH+ colon cancer stem cells and increased differentiation of stem cells

Abstract: BackgroundTumorigenesis is driven by stem cell (SC) overpopulation. Because ALDH is both a marker for SCs in many tissues and a key enzyme in retinoid acid (RA) signaling, we studied RA signaling in normal and malignant colonic SCs.HypothesisRA signaling regulates growth and differentiation of ALDH+ colonic SCs; dysregulation of RA signaling contributes to SC overpopulation and colorectal cancer (CRC) development.MethodsWe analyzed normal and malignant colonic tissues and CRC cell lines to see if retinoid rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 31 publications
7
57
0
Order By: Relevance
“…Similar findings were found in colon CSCs overexpressing ALDH. Indeed, the authors found that ATRA treatment inhibited colonic CSC proliferation, decreased the ALDH hi population size, induced differentiation of CSC, and reduced metastasis formation [265]. Moreover, the authors imputed the CSCs establishment due to dysregulation of ATRA signaling.…”
Section: Tumor Progression: Cscs and Invasionmentioning
confidence: 99%
“…Similar findings were found in colon CSCs overexpressing ALDH. Indeed, the authors found that ATRA treatment inhibited colonic CSC proliferation, decreased the ALDH hi population size, induced differentiation of CSC, and reduced metastasis formation [265]. Moreover, the authors imputed the CSCs establishment due to dysregulation of ATRA signaling.…”
Section: Tumor Progression: Cscs and Invasionmentioning
confidence: 99%
“…And during CRC development, dysregulation of these kinetic mechanisms induces changes in crypt cell quiescence associated with the increased number of proliferative cells that occurs in colonic tumors. We also know that ALDH is a key component of the retinoid signaling pathway and ALDH-positive SCs directly differentiate into neuroendocrine cells [51]. Thus, we hypothesize that upregulated miRNA92a, by down-regulating LRIG1, decreases differentiation and increases proliferative potential of ALDH-positive CSCs.…”
Section: What Is the Role Of Mirna92a In The Stem Cell Origin Of Cancer?mentioning
confidence: 89%
“…ALDEFLUOR Assay, Propidium Iodide Staining and EpCAM Staining of Normal and Tumor cells. ALDEFLUOR-positive cells were isolated as described previously [5,17,51,56]. The dissociated cells from both normal and tumor were washed thrice in sterile HBSS and then subjected to the ALDELFUOR Assay following the manufacturer's protocol (STEMCELL Technologies Inc., BC, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…ATRA is an active metabolite of vitamin A and involved in many crucial signaling pathways such as embryonic development, immune system function, reproduction, and epithelial integrity [124][125][126]. ATRA is commonly used as a differentiation agent in stem cell research [127,128], and several studies have reported the use of ATRA as a differentiation agent to inhibit cancer cell growth by altering the cell cycle progression [129][130][131] and to target CSCs tumorspheres in various malignancies both in vitro and in vivo [132][133][134][135][136]. In OC, ATRA reduced ALDH1 expression and suppressed in vitro tumorsphere formation, cell migration, and invasion and in vivo tumorigenesis [106] ( Table 2).…”
Section: All-trans Retinoic Acid (Atra)mentioning
confidence: 99%